New process of silicon carbide purification intended for silicon passivation. (January 2017) - Barbouche, M.; Zaghouani, R. Benabderrahmane; Benammar, N.E.; Aglieri, V.; Mosca, M.; Macaluso, R.; Khirouni, K.; Ezzaouia, H.
Abstract: In this work, we report on a new, efficient and low cost process of silicon carbide (SiC) powder purification intended to be used in photovoltaic applications. This process consists on the preparation of porous silicon carbide layers followed by a photo-thermal annealing under oxygen atmosphere and chemical treatment. The effect of etching time on impurities removal efficiency was studied. Inductively coupled plasma atomic emission spectrometry (ICP-AES) results showed that the best result was achieved for an etching time of 10 min followed by gettering at 900 °C during 1 h. SiC purity is improved from 3N (99.9771%) to 4N (99.9946%). Silicon carbide thin films were deposited onto silicon substrates by pulsed laser deposition technique (PLD) using purified SiC powder as target. Significant improvement of the minority carrier lifetime was obtained encouraging the use of SiC as a passivation layer for silicon. Highlights: It's possible to produce porous SiC thin film by acid vapor etching. It's possible to improve the purity of SiC particles by a new method based on three steps: - Formation of porous SiC thin film by vapor etching. - Gettering of impurities from the volume to the surface by rapid thermal annealing. - Elimination of this porous thin film by chemical etching. Quality of purified SiC depends on time of vapor etching. Effective minority carrier lifetime increase after deposition of purified SiC into silicon substrate. Passivation of silicon is better with purified SiC than with no-purified SiC.